Gastrointestinal helminths of Adélie penguins (Pygoscelis adeliae) from Antarctica - Diaz, Julia I.; Fusaro, Bruno; Longarzo, Lucrecia; Coria, Néstor; Vidal Burgos, Virginia; D'Amico, Verónica L.; Barbosa, Andrés (Polar Research, 2016)
Knowledge about parasitic organisms in Antarctica is scarce and fragmentary. The study reported here adds to the knowledge of gastrointestinal parasites of the Adélie penguin (Pygoscelis adeliae) (Sphenisciformes), from 25 de Mayo/King George Island (South Shetlands), Bahia Esperanza (Hope Bay) and Avian Island (Antarctica). Thirty-five freshly dead specimens (20 chicks and 15 adults) were collected from December 2007 to December 2014 and examined for internal macroparasites. Three adult parasite species were found: one Cestoda, Parorchites zederi, and two Nematoda, Stegophorus macronectes and Tetrameres sp. Immature Tetrabothrius sp. were found in hosts from Avian Island. Helminth communities are known to be related to host feeding behaviours. Low parasite richness observed in Adélie penguins could be related to the stenophagic and pelagic diet of this host species, which feeds almost exclusively on krill. Financial support was given by the Dirección Nacional del Antártico (DNA), the Spanish Ministry of Economy and Competitiveness, and European Regional Development Fund (projects CGL2007-60369 and CTM2011-24427). VV was supported by a PhD grant from the Spanish Council of Scientific Research (JAEPre08-01053). Peer reviewed